Association between fine particulate matter exposure and subclinical atherosclerosis: A meta-analysis. (April 2016) - Akintoye, Emmanuel; Shi, Liuhua; Obaitan, Itegbemie; Olusunmade, Mayowa; Wang, Yan; Newman, Jonathan D; Dodson, John A
Background: Epidemiological studies in humans that have evaluated the association between fine particulate matter (PM2.5 ) and atherosclerosis have yielded mixed results. Design: In order to further investigate this relationship, we conducted a comprehensive search for studies published through May 2014 and performed a meta-analysis of all available observational studies that investigated the association between PM2.5 and three noninvasive measures of clinical and subclinical atherosclerosis: carotid intima media thickness, arterial calcification, and ankle-brachial index. Methods and results: Five reviewers selected studies based on predefined inclusion criteria. Pooled mean change estimates and 95% confidence intervals were calculated using random-effects models. Assessment of between-study heterogeneity was performed where the number of studies was adequate. Our pooled sample included 11, 947 subjects for carotid intima media thickness estimates, 10, 750 for arterial calcification estimates, and 6497 for ankle-brachial index estimates. Per 10 µg/m 3 increase in PM2.5 exposure, carotid intima media thickness increased by 22.52 µm but this did not reach statistical significance ( p = 0.06). We did not find similar associations for arterial calcification ( p = 0.44) or ankle-brachial index ( p = 0.85). Conclusion: Our meta-analysis supports a relationship between PM2.5 and subclinical atherosclerosis measured by carotid intima media thickness. We did not find a similar relationship between PM2.5 and arterial calcification or ankle-brachial index, although the number of studies was small.